7.0k views
2 votes
Simplify (-6^1/3)^(-2)=

User Langen
by
5.1k points

1 Answer

4 votes

For this case we must simplify the following expression:

(
(-6 ^ {\frac {1} {3}}) ^ {- 2}

So, by definition of power properties we have:


a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}

Then, rewriting the expression:


\frac {1} {(- 6 ^ {\frac {1} {3}}) ^ 2} =\\\frac {1} {(- 6 ^ {\frac {1} {3}}) * (- 6 ^ {\frac {1} {3}})} =\\\frac {1} {(6 ^ {\frac {1} {3}}) * (6 ^ {\frac {1} {3}})} =\\\frac {1} {6 ^ {\frac {2} {3}}}

ANswer:


\frac {1} {6 ^ {\frac {2} {3}}}

User TAbdiukov
by
6.0k points